Assistance for Construction of Rainwater Infiltration Wells through Rain Water Harvesting in Overcoming Flood Prone in Beji Village, Depok City - Widiastuti, Ika (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Beji Village is one of the villages in Beji District, Depok City. Currently, Beji Village is quite dense with residents. Most of the land is used as housing for residents, so it has an impact on depleting the availability of vacant land as water catchment areas. This causes the area to become prone to flooding. This service aims to assist the people of Beji, Depok, build rainwater infiltration wells through Rain Water Harvesting to overcome flood proneness. Participatory Rural Appraisal (PRA) is used in this assistance by inviting the community to participate in Extension and Education, Training and Guidance, Field Assistance, Community Involvement, Research and Monitoring, and Partnership Development. This service resulted in rainwater harvesting, which has absorption two times faster than before. It can be illustrated that rainwater will usually recede within half an hour at the service location. With this infiltration well, incoming rainwater can recede within 10-15 minutes for a field area of approximately 80 m2. With this infiltration well, rainwater that usually recedes within half an hour can recede within 10-15 minutes for a field area of 80 m2. This shows the success of community service in reducing the risk of flooding in Beji Village and providing effective solutions to address the problem of water availability and water management in the area.